CAMPUR KODE PADA MEDIA SOSIAL â€œFACEBOOKâ€ - TOLOLIJU, AMELIA JOLINDA; MARENTEK, ANDRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â  The research is entitled â€œCode Mixing in the Social Media Facebookâ€. It is an attempt to analyze and explain the code mixing analysis in the social media Facebook. The objective of this research is to identify, classify, and analyze the code mixing on status and caption photos/videos in Facebook.Â Â Â Â Â Â Â Â Â Â Â  The writer conducts this research by using the descriptive method. In collecting the data, the status and caption photos/videos were taken from Facebook social media. To identify and classify the writer used theory by Muysken (2000) and Suwito (1985), and the data were analyzed and described by using the theories of Hoffman (1991) and Suwito (1983).Â Â Â Â Â Â Â Â Â Â Â  The results of this research show that in code mixing there are 65 research data. The types of code mixing the writer found out were 4 types of code mixing included existing data, according to Muysken (2000), namely insertion of word, insertion of phrase and alternation. And according to Suwito (1985), the whole data is external code mixing, which is code mixing from the Indonesian language to the foreign language that is English language. Based on the cause of the occurences of code mixing the writer found out 13 cause of occurance of code mixing according to theory by Hoffman (1991:96) and Suwito (1983) there were talking about particular topic, quoting somebody else, being emphatic about something, interjection, repetition used for clarification, intention of clarifying, expressing group identity, to soften or strengthen request or command, because of real lexical need, to exclude other people when a comment is intended for only a limited audience, role factor, variability factor, the desire factor to explain and interpret.----------------------------------------------------------------------Keywords: Sociolinguistics, Code Mixing, Facebook